ANALISIS PENANGANAN KELUHAN PELANGGAN DI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA HIDAYAH KOTA BENGKULU - Qomariah, Nurul Qori Irma; Adriadi, Rekho (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
Responsiveness is one of the dimensions of service quality that is important for assessing the extent to which service providers can respond to customer requests and complaints quickly and appropriately. This research aims to determine the responsiveness of public services in handling customer complaints at PDAM Tirta Hidayah, Bengkulu City. The method used in this research is a qualitative method with a descriptive approach. The theory used in this research is the Responsiveness theory from Zeithml, using 4 theoretical indicators, namely, ability to respond to society, speed of service, accuracy of service, and timeliness of service. The results of the research show that PDAM Tirta Hidayah, Bnegkulu City has attempted to increase responsiveness in handling customer complaints, but based on findings in the field, PDAM Tirta Hidayah still lacks response in terms of timeliness in making service improvements to customers. These findings are expected to provide input for PDAM Tirta Hidayah in improving service quality and customer satisfaction. Keywords: Responsiveness, Public Service, Customer Complaints